The Behavior of Adolescents in Watching Violent Films - K. Pandjaitan, Nurmala; ., Nando (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2012)
In recent years many scenes of violence shown in films. Fights, beatings, murders, destructive, and harmful to others has always appeared in the film. Increasing the proportion of violent scenes in movies gave the negative influence of criticism for the audience. Anxiety about the emergence of negative influence is increasing due to the characteristics of a predominantly adolescence audience. One of the alleged negative impact on adolescence movies is aggression behavior. The purpose of this study were (a) know the behavior of adolescents in watching violent films (b) know the behavior of adolescents in the act of aggression (c) analyze the relationship between adolescent behavior in watching violent films with aggression behavior. The research subjects were 45 student of SMK Pelita Ciampea, Bogor. Research data are analyzed using Chi Square with contingency coefficient (C) ranges from 0-1. Behavior watching violent films do not have a significant relationship with the behavior of adolescent aggression. Intensity factor to aggression behavior in the family environment, in the neighborhood and situational factors has a significant relationship to adolescent aggression behavior at ? 0.01 with 99 percent confidence interval so that a positive relationship. Intensity factor to aggression behavior by friends to have a significant relationship with adolescent aggression behavior at ? 0.05 with 95 percent confidence interval so that a positive relationship.